The Influence of GCG On Financial Distress Of State-Owned Companies On The IDX In 2021-2024 - Setyowati, Wahyu; Supadmini, Sri; Fatmawati, Ananda Etika; Dwiastuti, Maria Magdalena Pur (Jurnal Kajian Akuntansi, Auditing dan Perpajakan, 2025)
The purpose of this study is to examine the influence of GCG (Good Corporate Governance), consisting of institutional ownership, managerial ownership, independent board of commissioners, board of directors, and audit committee variables on financial distress. This study is descriptive quantitative. The type of data used is secondary data, including the financial statements of state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024, obtained through the IDX website at www.idx.co.id. Data were collected using documentation techniques. The research sample consisted of state-owned enterprises listed on the Indonesia Stock Exchange from 2021 to 2024, selected using a purposive sampling method , resulting in a sample size of eight companies. The results of the study show that institutional ownership and independent board of commissioners variables partially have no effect on financial distress, and managerial ownership, board of directors, and audit committee partially have an effect on financial distress.